The Role of Accountants in Carbon Accounting to Support Energy Resilience Amid Global Geopolitical Dynamics - Sylvia Marcellina; Budi Mulia Kurniawan; Ameliya Silaning Utami; Novia Rosita; Yanuar Ramadhan (PT Keberlanjutan Strategis Indonesia, 2026)
This study examines the role of accountants in leveraging carbon accounting as a strategic instrument to support energy security amidst global geopolitical dynamics. A qualitative descriptive approach was employed through a systematic literature review guided by the PRISMA framework, with data collected from various international academic databases covering publications from 2021 to 2026. Articles were selected based on relevance, indexing quality, and methodological clarity. The findings indicate that carbon accounting has evolved from a compliance-oriented reporting tool to a strategic information system that supports environmental transparency, energy efficiency, and managerial decision-making. Accountants are shown to play an increasingly central role in transforming carbon data into actionable strategic insights, particularly in managing energy risks generated by geopolitical tensions. However, implementation in Indonesia remains constrained by limited integration between accounting and energy management systems, a weak regulatory framework, and inadequate sustainability competencies among accounting professionals. The study concludes that integrating carbon accounting with the strategic role of accountants is crucial for strengthening corporate energy security, and recommends further empirical research in high-emission and energy-intensive sectors to validate the proposed integrative framework.